Risk of new-onset inflammatory bowel disease in psoriasis patients treated with five different interleukin inhibitors: a systematic review and meta-analysis - Zhang, Jia-Xin; Li, Wen-Wei; Huang, Long-Zhuan; Lai, Sha; Qiu, Zhi-Kun (Frontiers in Immunology, 2025)
BackgroundInterleukin inhibitors represent a standard therapeutic approach for psoriasis. However, there is still debate about the risk of new-onset inflammatory bowel disease (IBD) in psoriasis patients following interleukin inhibitor treatment. This systematic review and meta-analysis aims to evaluate the risk of new-onset IBD in psoriasis patients treated with five interleukin inhibitors (Bimekizumab, Ixekizumab, Secukinumab, Brodalumab, and Ustekinumab), providing insights to inform clinical decision-making.MethodThis study was registered in the PROSPERO with registration number of CRD42024608423. The databases PubMed, Embase, Cochrane Library, and Web of Science were comprehensively searched for observational studies published as full-length papers in English. The Mantel-Haenszel method with a fixed-effects model and risk difference was used to compare the risk of new-onset IBD between experimental groups (using interleukin inhibitors) and the control groups (using placebo or non-interleukin inhibitors). Sensitivity analysis was performed using the leave-one-out method for the meta-analysis. Additionally, considering the potential for underdiagnosis of IBD, a meta-analysis of the risk of diarrhea was conducted.ResultThis study included 17 articles covering 21 Randomized Controlled Trials(RCTs). A total of 22 new-onset IBD cases were reported in the experimental groups, with 3, 14, 4, 1, and 0 cases in the Bimekizumab, Ixekizumab, Secukinumab, Brodalumab, and Ustekinumab group, respectively. The control group only reported 1 case of new-onset IBD. No significant difference in the risk of new-onset IBD was found between these experimental groups and control groups. Based on the fixed-effects model, the pooled risk difference for Ixekizumab group was MH RD 0.0027 (95% CI 0.0001-0.0054, I² = 0%, P = 0.04). Sensitivity analysis indicated that the data was stable. Regarding diarrhea, a total of 95 cases were reported in the experimental groups, compared to 50 cases in the control groups. The experimental groups of Bimekizumab, Secukinumab, and Brodalumab reported 49, 45, and 1 case of diarrhea, respectively, while their control groups reported 11, 39, and 0 cases, respectively. Based on the fixed-effects model, compared to the control groups, there were no significant differences in the risk of diarrhea among psoriasis patients treated with these three interleukin inhibitors, and sensitivity analysis demonstrated good data robustness. Additionally, no cases of diarrhea were reported in the Ixekizumab group and Ustekinumab group.ConclusionsThere is insufficient evidence to confirm that Ustekinumab, Bimekizumab, Secukinumab, and Brodalumab significantly increase the risk of new-onset IBD. However, compared to the control group, Ixekizumab was significantly associated with an increased risk of new-onset IBD in psoriasis patients. Psoriasis patients receiving Ixekizumab treatment should remain vigilant for gastrointestinal symptoms, particularly in high-risk patients, to identify and manage potential IBD early. Additionally, compared to the control group, no significant difference was observed in the risk of diarrhea as an adverse event among patients treated with Bimekizumab, Secukinumab, and Brodalumab.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024608423, identifier CRD42024608423.